Disgrace - Coetzee, J. M. 1940- (Vintage, 2000)
Fifty-two-year-old David Lurie, having lost his job and the respect of his friends and ex-wife after an affair with one of his students, retreats to his daughter's isolated small holding in South Africa where he attempts to relate to her and a society with new racial complexities.
Keywords: Pères et filles - Afrique du Sud - Romans, nouvelles, etc; Vie à la ferme - Afrique du Sud - Romans, nouvelles, etc; Vétérinaires - Afrique du Sud - Romans, nouvelles, etc; Farm life -- Fiction; Fathers and daughters -- Fiction; Teacher-student relationships -- Fiction; Veterinarians -- Fiction; Afrique du Sud - Romans, nouvelles, etc; Südafrika (Staat); South Africa -- Fiction; Fiktionale Darstellung; Domestic fiction